The Urgency of Knowledge of The History of The Langkat Sultancy Social Revolution for The Youth of Langkat - Ahmad Fuadi; Hayatun Sabariah; Muhammad Sufawi (Yayasan Ilomata, 2022)
History in the form of material during the Langkat Sultanate with an important instrument in tracing an event and as tangible evidence of the history that occurred. Sultanate of Langkat which was established on 12 Rabiul Awal in 1320 H. Coinciding with June 13, 1902 AD The research technique that the author did was through a historical approach with research methods in the form of heuristics (data collection), criticism (external and internal), interpretation, architectural analysis (morphology, stylistics, technology, environment, cultural acculturation) and historiography (historical writing). The data collection technique that the author uses is through interviews, literature studies and direct observation to the location of the research object. Based on the research that the author did, it was found that the Langkat Sultanate Revolution for young people was more characterized by modernity as evidenced by the more attractive style of Malay dress. Various architectural arts of the Langkat Sultanate and have officially become cultural heritage objects in 2010 with the mosque identity number 01.5.02.05.11.00000.